Berkah Kyai Dan Kesamaan Alumni: Studi Komparatif Keharmonisan Keluarga Santri Alumni Pondok Pesantren Al-Falah Kediri - Lailatul Fitriah (Social Science Academic, 2026)
The challenges of family resilience in the modern era require a deep understanding of the determining factors of household harmony, especially within specific subcultural communities such as Islamic boarding school (pesantren) alumni. This study examines the determinants of household harmony among pesantren alumni, focusing on modern challenges to family resilience. Specifically, it analyzes differences in family harmony based on four variables: marriage contract authority, the couple's alma mater background, the partner selection method, and marriage duration. Employing a quantitative comparative design, this research involved a sample of 42 pesantren alumni (N = 42) selected through purposive sampling. Data were collected using an adapted Family Harmony Scale (FHS-24) and analyzed using independent sample t-tests and one-way ANOVA. The inferential analysis reveals significant differences across the observed variables. First, couples married by a Kyai exhibit higher harmony scores than other groups. Second, couples sharing the same pesantren alma mater score significantly higher than those from different backgrounds. Third, regarding partner selection, self-chosen couples show higher harmony scores, followed by pesantren matchmaking, while family matchmaking scores the lowest. Lastly, differences were observed based on marriage duration, where the moderate-duration group scored higher compared to newlyweds and long-married groups. This study suggests that among the surveyed pesantren alumni, variance in family harmony is closely linked to both individual agency in partner selection and specific socio-religious factors, such as the blessing of religious authority and a shared educational background.